2019
DOI: 10.1111/cyt.12685
|View full text |Cite
|
Sign up to set email alerts
|

Fine needle aspiration cytology of paediatric soft tissue tumours highlighting challenges in diagnosis of benign lesions and unusual malignant tumours

Abstract: Introduction The type of soft tissue lesions seen in children differs from that seen in adults. The role of fine needle aspiration (FNA) cytology in their diagnosis is not well documented. Aim To study the cytopathological spectrum of paediatric soft tissue tumours to highlight uncommon benign and malignant lesions and the challenges in their diagnosis. Methods A 3‐year retrospective audit of all paediatric soft tissue FNA cytology cases from 2015 to 2017 was performed. Smears were reviewed along with cell blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 9 publications
0
3
0
2
Order By: Relevance
“…Sin embargo, las biopsias por punción pueden servir como una herramienta útil en el diagnóstico preoperatorio del lipoblastoma 16,17 y pueden realizarse con anestesia mínima. Para los patólogos es más dificultoso identificar y clasificar, de manera segura, las lesiones de partes blandas por el material obtenido en una biopsia por punción (especialmente en una punción con aguja fina), pero esto se puede realizar con bastante seguridad.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Sin embargo, las biopsias por punción pueden servir como una herramienta útil en el diagnóstico preoperatorio del lipoblastoma 16,17 y pueden realizarse con anestesia mínima. Para los patólogos es más dificultoso identificar y clasificar, de manera segura, las lesiones de partes blandas por el material obtenido en una biopsia por punción (especialmente en una punción con aguja fina), pero esto se puede realizar con bastante seguridad.…”
Section: Resultsunclassified
“…Para los patólogos es más dificultoso identificar y clasificar, de manera segura, las lesiones de partes blandas por el material obtenido en una biopsia por punción (especialmente en una punción con aguja fina), pero esto se puede realizar con bastante seguridad. 17 La edad de presentación, el examen histopatológico y los marcadores cromosómicos son los tres factores que ayudan a llegar al diagnóstico patológico final.…”
Section: Resultsunclassified
“…Difficulties are seen in accurately subtyping the tumors according to cell of origin, separating benign lesions from low grade sarcomas as well as correctly subclassifying the sarcoma. [21][22][23] Review of the cases with discordant diagnosis demonstrates some of the pitfalls which makes cytological diagnosis challenging. Few of these cases are briefly discussed in Table 5.…”
Section: Discussionmentioning
confidence: 99%
“…Larger studies have shown that category of spindle cell lesions is the most challenging to diagnose. Difficulties are seen in accurately subtyping the tumors according to cell of origin, separating benign lesions from low grade sarcomas as well as correctly subclassifying the sarcoma 21–23 . Review of the cases with discordant diagnosis demonstrates some of the pitfalls which makes cytological diagnosis challenging.…”
Section: Discussionmentioning
confidence: 99%
“…In our case, as like as in previously reported 5-year-old boy case, biopsy was inefficacious because of collection of nonrepresentative tissue. Recently, Agrawal et al 14 reported fine needle aspiration citology of pediatric soft-tissue lesions and neoplasms as a first-line investigation. Anyway, in his study, histopathology provided more accurate subtyping than fine needle aspiration in 8/25 cases, all benign diagnoses as myxoma and lipoblastoma.…”
Section: Discussionmentioning
confidence: 99%